Refining channel and power allocation for green device-to-device communications. (28th May 2020) - Hsu, Chih-Shun
Most of the existing researches for D2D communications try to achieve the minimum total transmission power of D2D user devices (DUEs) by performing channel assignment first, and then performing power control according to the QoS requirement of each DUE. However, after power control, the transmission powers and interferences of DUEs have dropped and the qualities of channels have changed, hence there is room to further reduce the transmission power of DUEs. To improve the existing works, the channel and power reallocations are performed for several rounds in the proposed schemes until the dropping transmission power is less than a threshold. Note that, the channel and power are not really allocated to the DUEs until the final refining allocation results are calculated by the base station. The trade-off among transmission power, throughput, and computation cost are discussed through extensive simulations. Simulation results justify the energy efficiency of the proposed refining schemes.